Blackpool in Film and Popular Music
X, 155 p. 15 illus., 11 illus. in color.
Keywords: This collection examines Blackpool, Britain’s first and largest working-class seaside resort as a location for the production and consumption of British film and popular music, and the meaning of ‘Blackpool’ in films and songs. It examines representation of Blackpool in films such as Hindle Wakes, A Taste of Honey, Bhaji on the Beach, Away, Bob’s Weekend, The Harry Hill Movie and Miss Peregrine's Home for Peculiar Children, linking it to the concepts of heterotopia, purgatory, fantasy, simulacra and the carnivalesque. It also presents music in Blackpool through the history of its venues and examines development of punk and grime music in this seaside town. The authors argue that Blackpool in filmic and musical texts often stands for British culture, but increasingly for culture which is remembered or imagined rather than present and real.